The Cold Ion Population at Geosynchronous Orbit and Transport to the Dayside Magnetopause: September 2015 to February 2016. Issue 11 (13th November 2019) - Denton, M. H.; Henderson, M. G.; Maruyama, N.; Fuselier, S. A.
Abstract: During intervals of enhanced magnetospheric convection, a high‐density plume of cold ions is eroded from the plasmasphere and can flow toward the dayside magnetopause where it has the potential to reduce the rate of magnetic reconnection. In any interval of long‐duration enhanced convection, tons of ions may follow such a trajectory. The study here concerns cold ion observations from geosynchronous orbit (GEO) during both calm and active periods. Probability distributions of the cold ion density and cold ion flow speed are determined during the 6‐month period from September 2015 to February 2016, inclusive. During low geomagnetic activity, the cold, dense ions are in corotation with the Earth, and flow speeds rarely exceed 10 km/s. During elevated geomagnetic activity, the cold ions between 12 and 18 magnetic local time are observed to flow toward the dayside magnetosphere with a speed of >10 km/s approximately 50% of the time. The Shue et al. (1998, https://doi.org/10.1029/98JA01103 ) model of the magnetopause location is used to derive the distribution of approximate minimum times for the cold ions to be transported from GEO to the dayside magnetopause. On average, during enhanced convection periods (Kp > 3) ions will take a mean time of 4.5 hr to travel from GEO to the dayside magnetopause. Key Points: Cold ion densities of 10 s/cm 3 and flow speeds in excess of 10 km/s from GEO to magnetopause during enhanced convection (Kp < 3) Plasma flows are directed to the dayside magnetopause approximately 50% of the time for Kp < 3 with plasma is in quasi corotation when Kp > 1 + Shue et al. model used to quantify minimum transit time (+ probability distributions) of cold ions from GEO to magnetopause